Standardisation of minimal processing techniques for selected vegetables - Shibi Varghese (Department of Processing Technology, College of Horticulture, 2006)
The study “Standardisation of minimal processing techniques for selected vegetables” was undertaken at the Department of Processing Technology, College of Horticulture, Kerala Agricultural University, with the objective of developing the protocol for minimal processing in seven vegetables viz, cowpea, brinjal, okra, elephant foot yam, pumpkin, ashgourd and drumstick. Shriveling, browning and rotting were the major causes of deterioration in storage of cut vegetables under ambient conditions. Surface sanitation with 30ppm sodium hypochlorite was found to be the most effective treatment for preserving visual quality, reducing microbial contamination and enhancing the shelf life of all the cut vegetables. Prestorage treatment of cut vegetables with chemical preservatives potassium metabisulphite / sodium benzoate coupled with acidulants ascorbic acid / citric acid was effective in reducing browning, retaining firmness and controlling decay in cut vegetables. The treatment combination of 0.1% each of potassium meta bisulphite and ascorbic acid was found to be superior to the other treatments in maintaining visual and keeping quality in fresh cut vegetables. The prestorage treatments brought about a four fold reduction in bacterial and a three fold reduction in fungal and yeast count as compared to control. Exposure of cut vegetables to gamma irradiation resulted in a six fold reduction in bacterial sand fungal and three fold reduction in yeast count. The optimum irradiation dose for maintaining visual quality and reducing microbial population was 200 Gy for precut okra, elephant foot yam, pumpkin, cowpea and drumstick and 100 Gy for ashgourd and brinjal. Shelf life of irradiated vegetables was not further extended when kept under refrigeration. Refrigerated storage significantly reduced the intensity of undesirable physical changes microbial deterioration and enhanced shelf life of cut vegetables. Unventilated polymeric films were found to be the ideal packaging material for cut vegetables, polypropylene for cowpea, ashgourd, elephant foot yam, pumpkin and drumstick and polyethylene for okra and brinjal in terms of visual attributes and shelf life. Packaging in polystyrene tray and wrapping with cling film can also be recommended for enhanced visual and keeping quality of minimally processed products. Shelf life obtained for pretreated and packed cut vegetables under refrigeration were nine days for cowpea, brinjal, okra, ashgourd, ten days for pumpkin, elephant foot yam and fourteen days for drumstick.